Theory Of Moral Development - Yahaya, Azizi (2006)
Abstract: Lawrence Kohlberg’s theory of moral development includes three levels: (1) a preconvention level, where judgments are based on self-interest. (2) A conventional level, where judgments are based on traditional family values and social expectations and (3) a post conventional level, where judgments are based on more abstract and personal ethical principles. According to Erik Erikson’s theory of emotional development, people go through eight life stages between infancy and old age, each of which involves a central crisis. Adequate resolution of each crisis leads to greater personal and social competence and a stronger foundation for solving future crises.